Effects of successive judo matches on fatigue and muscle damage markers - Detanico, D.; Dal Pupo, J.; Franchini, E.; dos Santos, S. G. (The Journal of Strength and Conditioning Research, 2015)
This study aimed to investigate the acute effects of simulated judo matches on fatigue and muscle damage markers. Twenty male judo athletes participated in this study. The athletes performed three 5-minute judo matches separated by 15 minutes of passive rest between each match. The following measurements were performed before and after each match: shoulder external/internal rotation isokinetic torque and countermovement jump (CMJ). Blood samples were taken before the first match and after the third match for serum creatine kinase (CK) and lactate dehydrogenase (LDH) analysis. T-tests for dependent samples and analysis of variance for repeated measures were used to compare the variables over the time; the level of significance was set at 0.05. An overall effect of the successive matches on shoulder internal (PTIN) and external (PTEX) rotation peak torque and CMJ performance was observed. PTIN and PTEX showed significant decreases in postmatch 2 and postmatch 3 when compared with the baseline (p < 0.01). Also, CMJ height declined in postmatch 2 and postmatch 3 (p < 0.01) when compared with the baseline. Serum CK and LDH activity increased significantly after the third match (p < 0.01). It was concluded that 3 successive judo matches induced a decline of peak torque and muscle power in the upper and lower limbs, respectively, and also provoked an increase of muscle damage markers. These findings may provide important knowledge for coaches and physical trainers to improve judo-specific strength training in both the upper and lower limbs.